The Indian species of Liophloeothrips Priesner (Thysanoptera, Phlaeothripidae) with one new species - Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2011)
Liophloeothrips Priesner is a small genus of leaf-feeding Phlaeothripidae that is related to the widespread genera Gynaikothrips and Liothrips. A key is presented to distinguish these three genera, together with a key to, and review of, the 13 species now recognized in Liophloeothrips from India. Liophloeothrips acaciae sp. n. is described from Karnataka State, collected from the dry flowers, leaves and bark of Acacia auriculiformis. Liophloeothrips tenebrosus Ananthakrishnan & Jagadish is placed as a new synonym of L. pavettae Ananthakrishnan & Jagadish. A lectotype is designated for Liophloeothrips cecidii Ananthakrishnan 1964.